Fetal serum α‐1 microglobulin for renal function assessment: comparison with β2‐microglobulin and cystatin C. (14th May 2013) - Nguyen, Claire; Dreux, Sophie; Heidet, Laurence; Czerkiewicz, Isabelle; Salomon, Laurent J.; Guimiot, Fabien; Schmitz, Thomas; Tsatsaris, Vassilis; Boulot, Pierre; Rousseau, Thierry; Muller, Françoise
ABSTRACT: Objective: To compare the prognostic value of fetal serum α 1‐microglobulin with that of β 2‐microglobulin and cystatin C for postnatal renal function. Method: Retrospective study of α 1‐microglobulin, β 2‐microglobulin, and cystatin C in fetal serum from 126 fetuses with congenital abnormalities of the kidney and urinary tract (73 and 53, respectively). Two groups were defined: group with normal renal function and group with renal failure. For live born infants, renal function was assessed on the basis of serum creatinine (cutoff 50 µmol/L) or glomerular filtration rate (cutoff 75 mL/min/1.73 m2) or both. In case of infant or fetal death, histological kidney lesions were considered. Results: Significant differences ( p  < 0.001) were observed for the three markers between fetuses with good renal prognosis and those with renal failure (34.4 mg/L vs 67.6 mg/L for α 1‐microglobulin, respectively; 3.9 mg/L vs 7.35 mg/L, for β 2‐microglobulin, respectively; and 1.67 mg/L vs 2.12 mg/L for cystatin C, respectively). Areas under receiver operator curves were used to compare the three markers, 0.96, 0.90, and 0.74 for β 2‐microglobulin, α 1‐microglobulin, and cystatin C, respectively. Conclusion: Although α 1‐microglobulin is significantly different in fetuses with good renal prognosis and those with renal failure, overall, it is a less reliable prognostic marker than fetal serum β 2‐microglobulin. © 2013 John Wiley & Sons, Ltd. Abstract : What's already known about this topic? Serum α 1‐microglobulin is considered as a good marker of postnatal renal function in children. We compared its value with those of fetal serum β 2‐microglobulin and cystatin C, which have been previously evaluated for prenatal diagnosis of congenital abnormalities of the kidney and urinary tract. What does this study add? Fetal serum α 1‐microglobulin was much less reliable than fetal serum β 2‐microglobulin in prognostic assessment of renal function.